Karyotypic characterization of RAG cell line - JOSHI, C J; RANK, D N; KANAKARAJ, P (The Indian Journal of Animal Sciences, 2014)
RAG an HPRT-deficient cell line, used in production of somatic hybrids, has been evaluated for its chromosome characteristics. The cell line was heteroploid with chromosome number ranging from 61 to 72 (mode=66). The RAG karyotype consisted of 48 normal and 18 eonstitutive maker chromosomes. Normal chromosomes rangted from 0 to 4% cell while marker chromosomes were consistently present in single copy. Because of marked similarity in the chromosome composition from eell to cell, the karyotype of RAG could be defined clearly.